Medical Journalism and Emergency Medicine - Safari, Saeed; Baratloo, Alireza; Yousefifard, Mahmoud (Archives of Academic Emergency Medicine, 2018)
Nowadays, many researches in the field of medicine are conducting all around the world and medical journalism is a way to share the results. In fact, dissemination of the related manuscripts can prevent the repetitive research or may even lead to conducting a better survey. Therefore high quality medical journals are considered as up-to-date resources for further investigations. Medical journals are propagating their papers in various media including television programs, newspapers, internet websites and different social media. So they can influence the government policy makers, health-care professionals and even public. Moreover, most researchers hear about medical discoveries for the first time through medical journals and their related social media. So as well a high quality journal can help to improve medical science, a journal of poor quality can be damaging and distorting. Indeed, popular journals have the power of inventing a â€œcommunication stormâ€ to draw attention to a certain topic. Thus they have to respect the accepted international principles to prevent spreading inaccurate and misleading data. This paper aims to review the previous and current situation of medical journalism by focus on field of emergency medicine.